ChemInform Abstract: Synthesis of Enantiopure 1, 2‐Azido and 1, 2‐Amino Alcohols via Regio‐ and Stereoselective Ring‐Opening of Enantiopure Epoxides by Sodium Azide in Hot Water. Issue 24 (27th May 2016) - Wang, Hai‐Yang; Huang, Kun; De Jesus, Melvin; Espinosa, Sandraliz; Pinero‐Santiago, Luis E.; Barnes, Charles L.; Ortiz‐Marciales, Margarita
Abstract: The ring‐opening of enantiopure aryl epoxides by azide anion takes place preferentially at the internal position to produce 2‐azido ethanols with high regio‐ and enantioselectivity.